Validity Instrument Test Based Computer Test Higher Order Thinking (Cbt-Hot) on Intermediate Reading Course - Anita Kurnia Rachman; Ike Dian Puspitasari; Indrawati Pusparini (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2022)
Higher Order Thinking is a skill that requires skills such as analyzing, evaluating, and creating. One way to develop high-order thinking skills in students is to get the problem solved in the form of problem solving, creative thinking and critical thinking.The good from this reasearch is to develop and create evaluation instrument of High Order Thinking (HOT) with Computer Based Test .The items developed have been validated theoretically and valid. Developed Instrument tests were tested on Students from intermediate reading class . Data Collection method used test method and questionnaire method. The data analysis technique used descriptive analysis technique which included analysis of High Order Thinking (HOT) test based on Computer Based Test (CBT ) to know the value of validity, reliability, homogenitas, and Annona . The result of question analysis have validity test with t-account > t-table (t-table =0.2573). While reliability value 0,628 for package 1, reliability value 0,651 for package 2 reliability value 0,721 for package 3, reliability value 0,582 for package 4, reliability value 0,839 for package 5 means the test reliable. From the homogeneous one-way Annona test, it is known that the significance value for each package is 0.000. Thus, P value is smaller than α = 0.05. So it can be concluded if Ho is rejected. It means, there is an effect on students’ thinking from the type of test given . Based on the result from research that done, so it can be concluded that evaluation instrument of High Order Thinking (HOT) with Computer Based Test (CBT) in intermediate reading courses are valid and reliable.